Características demográficas de los migrantes búlgaros y rumanos en España - Concepción Domingo Pérez (Cuadernos de Geografía de la Universitat de València)
The migratory flow from, above all, Romania has reached in Spain the first place among the various groups of immigrants. Their demographic characteristics are similar to the set of migratory flows being a young population and a slightly higher proportion of males. However, the uniqueness of Romanians, Bulgarians and other nationalities in Eastern Europe is that their demographic structures and growth rates respond to mature population that are lossing a considerable number of young people. Moreover, in Spain, as host country, they involve the incorporation into society of groups that provide dynamism in labour market, in their geographical distribution and, especially, in increasing fertility.